RESPON MAHASISWA PENDIDIKAN SOSIOLOGI FKIP UNTAN TENTANG UJARAN KEBENCIAN DI MEDIA SOSIAL - Kelin, Fransiska Yolanda; Imran, Imran; Ramadhan, Iwan (Universitas Tanjungpura, 2023)
This study aims to find out how the Sociology Education FKIP Untan students respond from the aspects of knowledge, assessment, and action regarding hate speech on social media. The research approach used is a qualitative approach with descriptive methods. Data collection techniques are interviews and documentation. Data collection techniques used are observation, interviews, and documentation. While the data collection tools used are observation guides, interview guides and documentation. In this study, it was presented in a qualitative descriptive manner using 4 informants from Sociology Education Students of FKIP Untan. The results of this study show that Sociology Education Students of FKIP Untan as human beings who have intellectual ability to realize this status in the realm of real life. The response from the knowledge aspect of FKIP Untan's Sociology Education Students saw and knew hate speech about religious insults and insulting skin color was a bad dead. The response from the aspect of the action of Sociology Education Students is to give a warning in the form of rejection of hate speech, insulting religion and insulting skin color to people who do it on social media.